Synthesis and Characteristics of Carbon Nanotube Using Plasma Arc Discharge - Mohamed Sultan, Suhana; Azahurin, Nurul Syazwani; Mohamad, Azam (ELEKTRIKA- Journal of Electrical Engineering, 2018)
Carbon nanoparticles (CNP) were synthesized in arc plasma discharge using a simple, low-cost and toxic-free precursor gas. The structural and electrical characteristics were examined. The diameter and the height of the grown CNP was 28.5 Î¼m and Â 316.7 Î¼m , respectively. SEM image showed existence of a high density and uniform nanostructures within the cylindrical bulk CNP tube. The average diameter of the nanoparticles is 600 nm. The electrical characteristics revealedÂ low resistance with R = 7.23 mÎ© with Cu electrodes.Â In addition, the device exhibited aÂ Â high conductivity of 6.8 x 105 Scm-1. These results indicate the potential of CNP material for power device applications.